2018
DOI: 10.1021/acs.biomac.8b00233
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Stabilization of Concentrated Edible Oil-in-Water Emulsions Based on Electrostatic Complexes of a Food-Grade Cationic Surfactant (Ethyl Lauroyl Arginate) and Cellulose Nanocrystals

Abstract: We report on high-internal-phase, oil-in-water Pickering emulsions that are stable against coalescence during storage. Viscous, edible oil (sunflower) was emulsified by combining naturally derived cellulose nanocrystals (CNCs) and a food-grade, biobased cationic surfactant obtained from lauric acid and L-arginine (ethyl lauroyl arginate, LAE). The interactions between CNC and LAE were elucidated by isothermal titration calorimetry (ITC) and supplementary techniques. LAE adsorption on CNC surfaces and its effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 51 publications
5
66
0
Order By: Relevance
“…Other publications are also in agreement with the use of cellulose in O/W emulsions using CNF chemically treated with lauroyl chloride [10] and CMF with essential oils that have antimicrobial functions [12]. Other stabilizers, such as quinoa starch granules, had the same ability to stabilize oil drops in food-grade Pickering emulsions [6] or CNC with a food-grade surfactant [27] to stabilize sunflower oil-in-water emulsions. In this last case, emulsions with a low surfactant addition (<0.03 wt% ethyl lauroyl arginate (LAE)) had the same droplets structure as stabilized emulsions, with around 65% OCEP and similar size distribution.…”
Section: Stability Toward Centrifugationsupporting
confidence: 60%
See 1 more Smart Citation
“…Other publications are also in agreement with the use of cellulose in O/W emulsions using CNF chemically treated with lauroyl chloride [10] and CMF with essential oils that have antimicrobial functions [12]. Other stabilizers, such as quinoa starch granules, had the same ability to stabilize oil drops in food-grade Pickering emulsions [6] or CNC with a food-grade surfactant [27] to stabilize sunflower oil-in-water emulsions. In this last case, emulsions with a low surfactant addition (<0.03 wt% ethyl lauroyl arginate (LAE)) had the same droplets structure as stabilized emulsions, with around 65% OCEP and similar size distribution.…”
Section: Stability Toward Centrifugationsupporting
confidence: 60%
“…In the food industry, Pickering emulsions using cellulose products as emulsifiers include cellulose nanocrystals chemically modified with octenyl succinic anhydride [26] or ethyl lauroyl arginate [27] and CMF modified with hydrophilic polymers (cellulose esters/ethers) or pretreated with enzymatical or carboxymethylation pretreatment as emulsifier/stabilizer in whipped toppings, sauces, foams, or bakery products [28,29]. In this way, cellulose is not digested by human beings, although it can be partially broken down into smaller components for absorption into the bloodstream and is considered as dietary fiber [30].…”
Section: Introductionmentioning
confidence: 99%
“…The gelatin molecules were probably saturated with LAE affecting the surface tension of FFS. This is consistent with Bai et al () who reported the surface tension of the aqueous solution to gradually decrease with the LAE concentration (0.001% to 0.6%, w/w) due to its cationic surfactant character.…”
Section: Resultssupporting
confidence: 92%
“…Xiang et al discovered that cellulose nanofibrils form more stable foams compared to cellulose nanocrystals, attributed to cellulose nanofibrils ability to spread into the bulk, ensuing enhanced interfacial and bulk elasticity (Xiang et al, 2019). Bai et al investigated the stabilization of concentrated edible oil-in-water Pickering emulsions by modifying the surface of naturally derived cellulose nanocrystals with a food-grade cationic surfactant (ethyl lauroyl arginate) (Bai et al, 2018). The researchers revealed that as surfactant-covered NCs are more hydrophobic, their surfaces impart lower surface tension and higher surface coverage, contributing to enhanced electrostatic stabilization and emulsifying ability.…”
Section: Surface Modification Of Nanocellullosementioning
confidence: 99%
“…Aside from their biocompatibility and abundance, another benefit of utilizing CNCs is that they can be easily modified. Various modification methodologies, encompassing covalent bonding through the insertion of functional chemical groups or surface active species (surfactants, polymers, or proteins) and non-covalent bonding through physical interactions such as electrostatic interaction, hydrogen bonding, and van der Waals force, have been developed to tailor their characteristics and enhance the emulsion stability (Hu et al, 2015b;Bai et al, 2018;Liu et al, 2018;Pindáková et al, 2019;. The CNCs functionalization controls the type of emulsion.…”
Section: Nanocellulose As Pickering Emulsifiersmentioning
confidence: 99%